2020
DOI: 10.3389/fphar.2020.593993
|View full text |Cite
|
Sign up to set email alerts
|

Elaphuri Davidiani Cornu Improves Depressive-Like Behavior in Mice and Increases Neurotrophic Factor Expression in Mouse Primary Astrocytes via cAMP and ERK-Dependent Pathways

Abstract: Elaphuri Davidiani Cornu (EDC) is the natural shedding horn of Elaphurus davidiauus Millne-Edwards that was used by people in ancient China for maintaining physical and mental health. We evaluated the antidepressant effect of EDC using depression-like animal models and explored possible mechanisms in mouse primary astrocyte cultures. We found that aqueous extracts of EDC significantly improved depression-like behavior in a mouse model of depression. The extracts enhanced expression of nerve growth factor and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Primary astrocyte cultures were prepared from the hippocampal tissue of postnatal BALB/c mice on day 1 as previously described [ 34 ]. Cell culture reagents for astrocytes were purchased from Thermo Fisher Scientific (Waltham, MA).…”
Section: Methodsmentioning
confidence: 99%
“…Primary astrocyte cultures were prepared from the hippocampal tissue of postnatal BALB/c mice on day 1 as previously described [ 34 ]. Cell culture reagents for astrocytes were purchased from Thermo Fisher Scientific (Waltham, MA).…”
Section: Methodsmentioning
confidence: 99%
“…Because of the rapid advancement of science and technology, the research on TCMs continues to deepen. Previous preclinical and clinical findings have revealed that free TCMs can play an essential role in treating the pathophysiology of many diseases, including cancer (Wang R. et al, 2020), diabetes , Alzheimer's disease , depression (Zhu et al, 2020), and COVID-19 (Pan et al, 2020;Tian J. et al, 2020). In addition, some researchers have begun to focus their study on how to treat CNS injuries more effectively by using exosomes as drug delivery vehicles, these carrying TCMs to specific areas and exerting therapeutic effects.…”
Section: Exosomes As Drug Delivery Vehicles For Traditional Chinese Medicines (Tcms)mentioning
confidence: 99%
“…As an important traditional Chinese medicine (TCM), EDC was first documented in Shennong Ben Cao Jing (approximately 200 B.C.-200 A.D.) and has been in TCM clinic use for thousands of years [6]. EDC was reported to have several biological activities, such as antiosteoporosis [7], antiaging [8], immuno-enhancing activity [9], and improving depressive-like behavior [6,10]. As the population of Père David's deer grows, the amount of shed EDC increases year by year [11], and it is expected to recover its medicinal value as soon as possible.…”
Section: Introductionmentioning
confidence: 99%